Search for long-lived doubly charged Higgs bosons in p(p)over-bar collisions at root s=1.96 TeV - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We present a search for long-lived doubly charged Higgs bosons (H±±), with signatures of high ionization energy loss and muonlike penetration. We use 292pb-1 of data collected in pp̄ collisions at s=1.96TeV by the CDF II detector at the Fermilab Tevatron. Observing no evidence of long-lived doubly charged particle production, we exclude HL±± and HR±± bosons with masses below 133GeV/c2 and 109GeV/c2, respectively. In the degenerate case we exclude H±± mass below 146GeV/c2. All limits are quoted at the 95% confidence level. © 2005 The American Physical Society.